A bipolar functionality of Q/N‐rich proteins: Lsm4 amyloid causes clearance of yeast prions. Issue 3 (20th March 2013) - Oishi, Keita; Kurahashi, Hiroshi; Pack, Chan‐Gi; Sako, Yasushi; Nakamura, Yoshikazu
Abstract Prions are epigenetic modifiers that cause partially loss‐of‐function phenotypes of the proteins in Saccharomyces cerevisiae. The molecular chaperone network that supports prion propagation in the cell has seen a great progress in the last decade. However, the cellular machinery to activate or deactivate the prion states remains an enigma, largely due to insufficient knowledge of prion‐regulating factors. Here, we report that overexpression of a [PSI+]‐inducible Q/N‐rich protein, Lsm4, eliminates the three major prions [PSI+], [URE3], and [RNQ+]. Subcloning analysis revealed that the Q/N‐rich region of Lsm4 is responsible for the prion loss. Lsm4 formed an amyloid in vivo, which seemed to play a crucial role in the prion elimination. Fluorescence correlation spectroscopy analysis revealed that in the course of the Lsm4‐driven [PSI+] elimination, the [PSI+] aggregates undergo a size increase, which ultimately results in the formation of conspicuous foci in otherwise [psi−]‐like mother cells. We also found that the antiprion activity is a general property of [PSI+]‐inducible factors. These data provoked a novel "unified" model that explains both prion induction and elimination by a single scheme.